New Notion of « Sustainable Littoral » in Morocco: A Case of the Rabat-Sale-Kenitra Region - Ibtissam Motib (European Scientific Journal, ESJ, 2020)
The Moroccan littoral constitutes of a particularly sensitive and complex geographic space, which is undergoing various and increasing pressures. Through its diversity and its ecological potential, it requires more attention in terms of its protection. Due to the significant importance of this space, it is coveted for many activities and forms of development but the process of managing the space remains difficult and calls for question. This paper aims to provide an overview of the degradation of the Moroccan littoral, particularly in the region of Rabat-Sale-Kenitra. It also provides some management measures more suited for the intrinsic characteristics of this space that can be taken into account to guarantee a sustainable littoral.